Effect of Feeding Fermented Rapeseed meal on the Serum Biochemical Constituentsand Immune Response of Commercial Broiler Chicken - Vasavi, Mende Ramya; Nagalakshmi, D.; Vidya, B.; Srilatha, T.; Raju, S. (Indian Journal of Animal Nutrition, 2025)
The present study was conducted to evaluate the effect of fermented rapeseed meal on serum biochemical parameters and immune response of commercial broiler chicken. Day old commercial broiler chicks were randomly allotted to 6 dietary treatments with 10 replicates of 5 chicks in each replicate. The birds were raised in battery brooders under uniform management and fed the respective diets from day one to 42 days of age. Control diet for pre starter (1-2 weeks), starter (3-4 weeks) and finisher (5-6 weeks) phases was the standard corn-soyabean meal and remaining 6 experimental diets were prepared by including raw and fermented rapeseed meal at 5, 10 and 15% inclusion level. Blood was collected from one bird per replicate at 37th day of age from brachial vein and serum was separated for estimation of serum biochemical constituents viz., total protein, albumin and globulin, creatinine, alanine transaminase (ALT), aspartate aminotransferase (AST) and to assess the humoral response by measuring antibody titer to ND vaccine. On 40th day, one bird from each replicate was selected randomly to assess the cell mediated immune (CMI) response by inter-digital skin test to phytohaemagglutinin phosphate (PHA-P). The data was subjected to one way analysis of variance and difference between the means was tested using Duncan’s multiple range test. Serum albumin, globulin, creatinine, AST/ALT ratio were not affected while inclusion of RSM/FRSM upto 15% in diet, while serum total protein was higher (P